The concept of " rhetorics " between Al-Jahiz and Ibn Wahab Al-Kateb - younis, Wadha; Jahjah, Ilham (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research tries to address the problem of Ibn Wahab Al-Kateb Types of Rhetorics according to Al-Jahiz and Ibn Wahab Al-Kateb accusing Abi Othman Al-Jahiz of not giving rhetorics what it is worth, and of not studying it thoroughfully. Ibn Wahab claimed completing what is missed through his detailed study of the types of rhetorics, which are, to a large extent, similar to the types of rhetorics according to Abi Othman.The later referred to the importance of the relation between pronunciation, meaning and the necessity of the accordance between the two. In addition, meaning is prior to pronunciation because it depends upon thought and contemplation. He describes the types of rhetorics in a pyramidal sequential through levels that stem-- and result-- from each other. Similarly, Ibn wahab considers that the types of rhetorics result from each other. These types, according to critics, are a process of a birth of these forms. Despite the big similarity of the types of rhetorics according to both Ibn Wahab Al-Kateb and Abi Othman Al-Jahiz, the first was not only a transcriber, but also he added and clarified in certain areas. He exclusively talked about writers and classified them in one of five: transcript writer, pronunciation writer, contract writer, judgment writer and management writer. He also mentioned the most important features that a transcript writer must have and divided writers into three levels. He extended in talking about the types of handwriting and the forms of pens. These issues were dropped by Al-Jahiz when talking about the types of rhetorics.